Decision Support for the Global Logistics Positioning - Chun-Wei, Lin; Sheng-Jie, Hsu (International Journal of Industrial Engineering: Theory, Applications and Practice, 2013)
According to the enterprise’s global operations, its global logistics system had to be cooperated. It is clear that the global logistics (GL) is more complicated than the local logistics. However, it lacks a generic structure for GL’s position to support its decision-making. Therefore, this article proposed a Global Logistic Positioning (GLP) framework by means of literatures review and practice experience. And, constructed the variables in this framework to be a Decision Support System (DSS), which is useful for the GLP decision-making. This DSS can suggest the decision-maker to decide the positions of the operation headquarters, research and development bases, production bases, and distribution bases. <span style="font-size: 10pt; color: black; font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-fareast-font-family: 新細明體; mso-ansi-language: EN-US; mso-fareast-language: ZH-TW; mso-bidi-language: AR-SA;" lang="EN-US">For efficiency, this article proposed a four-phase algorithm which integrates the goal programming, revised <span style="font-size: 10pt; color: black; font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-fareast-font-family: 新細明體; mso-ansi-language: EN-US; mso-fareast-language: ZH-TW; mso-hansi-font-family: 新細明體;" lang="EN-US">Analytic Hierarchy Process method,<span style="font-size: 10pt; color: black; font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-fareast-font-family: 新細明體; mso-ansi-language: EN-US; mso-fareast-language: ZH-TW; mso-bidi-language: AR-SA;" lang="EN-US"> Euclidean distance, and Fitness concept, to execute the GLP computation. Finally, by a virtual example: ABC Company, to verify the GLP theoretical feasibility.